Personal Documents Exercise - Roy, William (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Select a personal document from another time or place the US in the twenty-first century. It can be from a publication, archive, family record, or other source. Personal document means diary, autobiography, letter, memoir, etc. A personal document from an ordinary person is preferable to public figure, though if you have a research interest that would make a public figure more appropriate, that is acceptable. Does this document fit into a particular genre (for example, salvation testimonial, rags to riches story, love letter, letter from the war, etc.)?